Small Molecule Inhibitors of Ceramidases - Essa M. Saied; Christoph Arenz (Cellular Physiology and Biochemistry, 2014)
The equilibrium between the pro-apoptotic ceramide and pro-vital sphingosine-1-phosphate is considered to be decisive for cell death or survival. The different ceramidases thus play key roles in cell fate and might offer attractive targets for pharmacological intervention. Although until recently only moderately active inhibitors have been described, first in vivo experiments suggest activity against cancer cell survival and multi-drug resistance. Here, we provide a brief overview on the different ceramidases, and we will review the known inhibitors and current strategies for further inhibitor development.